Pengabdian Kepada Masyarakat: Belajar Segitiga dan Segiempat melalui Pembelajaran Kontekstual berbantuan Gambar Puzzle Rumah Ulin - Besse Intan Permatasari; Tri Astuti Nur'aini; Prita Indriawati; Rahayu Sri Waskitoningtyas (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
One of the goals of learning mathematics is to be able to use flat plane concepts in solving everyday life problems. Mathematics learning that can bring the real world into the classroom is necessary. PKM is carried out to provide meaningful learning experiences and local cultural insights to students of PKBM Ans Noor Assalam B Package Equality Program so that they can achieve learning goals effectively. PKBM Ans Noor Assalam is a non-formal educational institution that organizes equality and homeschooling programs. Contextual learning with puzzle implemented through face-to-face learning on flat plane: triangular and quadrilateral shapes for the student of the Ans Noor Assalam Package B Equality Program. The learning result test is carried out at the end of the lesson to determine the achievement of the learning. The study test showed that learning was carried out well, and only one student was included in the incomplete category. Overall, the students are enthusiastic about participating in learning and are actively involved. Residents learn to easily understand the concept of triangles and quadrilaterals. Contextual learning with Rumah Ulin puzzle is well implemented and helps students learn to hone their mathematical concept abilities.